Pengaruh Inflasi, Produk Domestik Regional Bruto Dan Investasi Terhadap Pengangguran Terdidik Di Provinsi Aceh - Linda Wahyuni; Murtala Murtala (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to analyze the effect of inflation, GDP, and investment on educated unemployment in Aceh province from 2008 to 2018. The data used in this study are Panel data. The method used to analyze the relationship between the independent variable and the dependent variable is the panel data regression method. The results partially show that inflation has a positive and significant effect on educated unemployment in the Government of Aceh Province, PDRB has a positive and significant effect on educated unemployment in the Government of Aceh Province, and Investment has a negative and significant effect on educated unemployment in the Government of Aceh Province. Simultaneously, Inflation, GRDP, and Investment have a negative and significant effect on Educated Unemployment in the Government of Aceh Province